INCOME ANALYSIS AND BUSINESS CONSTRAINTS IN THE KELILING RICE REFINERY IN GAMPONG MEUNASAH BARO MUARA BATU DISTRICT NORTH ACEH DISTRICT (Case Study: The Efforts of Mr. Saiful Mahdi) - Irma Dahliana; Zuriani Zuriani; Fadli Fadli (Jurnal Mahasiswa Agribisnis, 2023)
The presence of mobile rice milling machine really helps the society in grinding their grains. However, the income earned on the mobile rice milling business is erratic, often many times slightly. This research aims to find out the income earned and the obstacles in the mobile rice milling business of Mr. Saiful Mahdi in Meunasah Baro Village, Muara Batu Sub-district, Aceh Utara Regency. This research uses descriptive quantitative data analysis methods to look at the income that is received, and descriptive qualitative to see business constraints. The results showed that the total cost is IDR 127,785,000/year, gross revenue is IDR 768,055,500/year, and net income is IDR 307,392,750/year. The value of R/C Ratio amounted to 6.01 and B/C Ratio are 2.41 shows that Mr. Saiful Mahdi's mobile rice milling business deserves to be kept. A common constraint encountered there is 4. Keywords: Mobile Rice Milling, Business Revenues, Business Constraints.